2023
DOI: 10.3390/foods12061316
|View full text |Cite
|
Sign up to set email alerts
|

Dough Rheological Behavior and Bread Quality as Affected by Addition of Soybean Flour in a Germinated Form

Abstract: This study analyzes the possibility of using soybeans as an addition to the main ingredients used to make bread, with the aim of improving its quality characteristics. To maximize the nutritional profile of soybeans they were subjected to the germination and lyophilization process before being used in bread making. The addition levels of 5%, 10%, 15%, and 20% germinated soybean flour (GSF) on dough rheology and bread quality were used. From the rheology point of view, the GSF addition had the effect of decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…WDWOC15% dough was characterized by the highest retardation time value. Atudorei et al [ 44 ] analyzed the possibility of using sprouted and dried soybeans as an addition to the main ingredients intended for bread production. The cited authors demonstrated a significant effect of the addition of 5%, 10%, 15% and 20% sprouted soy flour (GSF) on dough rheology and bread quality.…”
Section: Resultsmentioning
confidence: 99%
“…WDWOC15% dough was characterized by the highest retardation time value. Atudorei et al [ 44 ] analyzed the possibility of using sprouted and dried soybeans as an addition to the main ingredients intended for bread production. The cited authors demonstrated a significant effect of the addition of 5%, 10%, 15% and 20% sprouted soy flour (GSF) on dough rheology and bread quality.…”
Section: Resultsmentioning
confidence: 99%
“…For bread technology, the amount of amylase in the dough contributes to liberating fermentable sugars for fermentation, which can interfere with the velocity of fermentation. Additionally, the enzyme acts in starch retrogradation properties, which can interfere with bread characteristics and modify the color of crumb and crust due to the Maillard reactions [50]. The strains B. licheniformis LMG 12363 (P), L. fermentum (S), P. pentosaceus (S), and S. cerevisiae (S2), showed activity for all analyzed enzymes and then were selected for quantitative enzymatic analysis and gluten electrophoresis.…”
Section: Qualitative and Quantitative Hydrolases Analysismentioning
confidence: 99%
“…Also, the contribution of 100 g products to the daily intake of principal nutrients was calculated. Several studies reported the use of sprouts as ingredients in functional foods, to improve the rheological properties of dough in bakery products, or antioxidant activity [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. However, according to our knowledge, no studies have reported the contribution of the consumption of functional products based on lupin sprouts to the required daily dose of food nutrients and the impact on the glycemic index of fortified products.…”
Section: Introductionmentioning
confidence: 99%